The Impact of Colonialism on the Islamic Education System: Changes in Education Systems in Colonized Regions Such as Indonesia, India, and North Africa - Irwandi Siregar, Hendra; Nurdin Malayu, Owi Ali; Nasution, Abdusima (Mauriduna: Journal of Islamic Studies, 2024)
This study examines the impact of colonialism on the Islamic education system in colonized regions such as Indonesia, India, and North Africa, using a literature review method. The research finds that colonialism brought significant changes to the Islamic education system, both structurally and curricular. In Indonesia, the influence of Dutch colonialism is evident in the introduction of Western-based formal education, which shifted the position of traditional madrasas, although these institutions managed to survive by adopting modern curricula. In India, British colonialism introduced Western education, influencing the madrasa system with the adoption of some modern elements in its teaching. Meanwhile, European colonialism in North Africa created a dynamic interplay between Islamic traditions and modernity, leading to changes that reflect a compromise between local values and foreign influences. In conclusion, colonialism not only transformed the landscape of Islamic education in these regions but also drove adaptation and innovation within Islamic educational institutions to maintain their relevance amidst changing times.